A semiactive vibration absorber (SAVA) for automotive suspensions. (20th February 2004) - Mo, C.; Sunwoo, M.
The paper reports the development of a practical and effective technique for the automatic regulation of a hydraulic semiactive vibration absorber (SAVA) for automobiles. The work relies on a consistent hydraulic model of the actuator dynamics that includes the effects of fluid compressibility and a (nonlinear) viscous loss characteristic. A bistate control algorithm is developed using a Lyapunov approach. The performance of the proposed control design was established experimentally on a vibrating test stand. The work provides evidence that the inexpensive hardware design makes it possible to improve the ride and handling performance.